Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Bagian Produksi (Studi Kasus pada PT. Citra Bumi Raya Jombang) - Deni Widyo Prasetyo (Fakultas Ekonomi Universitas Yos Soedarso, 2023)
This study aims to analyze the effect of work discipline and work motivation on employee performance in the production department at PT. Image of Bumi Raya Jombang. This study uses the type of explanation (explanatory research) with a quantitative approach. The population in this study were production employees, totaling 35 people. The sampling technique in this study used a saturated sample. Method of data collection by distributing questionnaires and documentation. Data analysis using validity test, reliability test, multiple linear regression, classical assumption test and hypothesis testing and the coefficient of determination (R2) with the help of SPSS version 21. Based on the results of the study indicate that the given work discipline is able to improve employee performance at PT. Image of Bumi Raya Jombang. The work motivation given is able to improve employee performance at PT. Image of Bumi Raya Jombang. Keywords: Discipline; Motivation; Employee Performance.